The Effect of TPB Factors and Religiosity on Generation Z’s Interest in the Gig Economy - Rahmadani, Alvina; Ika Khusnia Anggraini (Journal of Development Economic and Social Studies, 2026)
This study examines the factors influencing the intention of Muslim Generation Z in Banyuwangi Regency to participate in the gig economy, utilizing the Theory of Planned Behavior (TPB) framework integrated with the Maqashid Shariah perspective. The variables analyzed include attitude, subjective norms, perceived behavioral control, and religiosity. Data were collected through an online survey of 150 respondents who met the research criteria and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS SEM). The results indicate that perceived behavioral control has a positive and significant effect, reinforcing the importance of individual capability and self-confidence in executing gig work. Attitude toward work flexibility also significantly influences participation interest. Conversely, subjective norms and religiosity show no significant effect, suggesting that participation decisions are driven more by personal factors rather than social pressure or religious values. From a Maqashid Shariah perspective, these findings reflect efforts toward the protection of intellect (hifz al-’aql), life (hifz an-nafs), and wealth (hifz al-mal) within the digital economy context.